Tooth ankylosis in man and the oxytalan fibre meshwork - Sims Milton R. (Sciendo, 1980)
There is no published information on the presence of the oxytalan fibre meshwork in the periodontal ligament of human ankylosed teeth. Contrary to the limited term experimental animal study of Hurst (1972), the present investigation demonstrates that extensive oxytalan structures can persist over many years in the presence of ankylosed teeth. Human biopsy material of four ankylosed first and second permanent molars exhibited a well-defined oxytalan meshwork that linked the teeth and periodontal vessels to each other proving that oxytalan-vascular associations are maintained in the absence of tooth oscillation. Thus, oxytalan fibres are not only found in connective tissues subject to stress (Fullmer et al. 1974), but also in the relatively stress-protected periodontium of submerged teeth. These findings raise new questions regarding the possible functional role of the oxytalan fibre meshwork.